Optimization of Phase-Change Material–Elastomer Composite and Integration in Kirigami-Inspired Voxel-Based Actuators - Decroly, Gilles; Raffoul, Romain; Deslypere, Clara; Leroy, Paul; Van Hove, Louis; Delchambre, Alain; Lambert, Pierre (Frontiers in Robotics and AI, 2021)
Phase-change materials--elastomer composites (PCMEC) actuators are composed of a soft elastomer matrix embedding a phase-change fluid, typically ethanol, in microbubbles. When increasing the temperature, the phase change in each bubble induces a macroscopic expansion of the matrix. This class of actuators is promising for soft robotics applications because of its high energy density and actuation strain, and its low cost and easy manufacturing. However, several limitations must be addressed, as the high actuation temperature and slow actuation speed. More, the lack of a consistent design approach limits the possibility to build PCMEC-based soft robots able to achieve complex tasks. In this work, a new approach to manufacture PCMEC actuators with different fluid-elastomer combinations without altering the quality of the samples is proposed. The influence of the phase-change fluid and the elastomer on free elongation and bending are investigated. We demonstrate that choosing an appropriate fluid increases the actuation strain and speed and decreases the actuation temperature compared with ethanol, allowing PCMEC to be used in close-contact with the human body. Similarly, by using different elastomer materials, the actuator stiffness can be modified, and the experimental results showed that the curvature is roughly proportional to the inverse of the Young’s modulus of the pure matrix. To demonstrate the potential of the optimised PCMEC, a kirigami-inspired voxel-based design approach is proposed. PCMEC cubes are moulded and reinforced externally by paper. Cuts in the paper induce anisotropy into the structure. Elementary voxels able of the basic kinematics are presented: bending, twisting, elongation, compression, and shear. Combining these voxels into modular and reconfigurable structures could open new possibilities towards the design of soft robots able of complex tasks.